Correlation Between D-Dimer Concentrations and Thromboelastography in Dogs With Critical Illness: A Retrospective, Cross-Sectional Study - Han, Hyun-Jung; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2022)
A hospital-based, retrospective, cross-sectional study was performed to assess the correlation of kaolin-activated thromboelastography (TEG) with D-dimer concentrations in 59 dogs with critical illness. Dogs were included if they had one or more serious disease detected upon performing TEG and D-dimer concentration determination based on the same blood sample. According to the coagulation index (CI), the 59 dogs were divided into two groups: a hypercoagulable state, with CI > 4 (44 dogs) and a normocoagulable state, with CI < 4 (15 dogs). Moreover, the 44 dogs with CI > 4 were divided into three sub-groups according to the disease etiology, i.e., inflammatory/tumor (I/T: 25 dogs), hemodynamic compromise (H: 11 dogs), and both conditions (I/TH: 8 dogs). The median values (interquartile ranges) of the CI and D-dimer concentration were 5.46 (4.55–6.33) and 410.25 (74.63–2206.12) in the 44 dogs with CI > 4 and 3.29 (2.92‒3.75) and 1164.7 (50‒2250.05) in the 15 dogs with CI < 4, respectively. The D-dimer concentration was significantly increased over the reference value in the 44 dogs with a CI > 4, particularly in dogs in the I/T group. It was also significantly increased in the 15 dogs with a CI < 4. D-dimer concentrations did not correlate with any of the TEG parameters in any of the dogs. Given this lack of correlation, the D-dimer concentration may be limited as an indicator of a possible hypercoagulable state in dogs with critical illness.